Contraceptive study: an assessment of contraceptive use in patients requesting termination of pregnancy at Chris Hani Baragwanath hospital - Nyakoe, Robert Barasa (My University, 2009)
The aim of this study was to assess the demographic characteristics and contraceptive practices of women requesting termination of pregnancy (TOP) at Chris Hani Baragwanath Hospital (CHBH). The study will provide insight into the reasons for contraceptive „failure‟ or non-use. Methods This is a cross sectional questionnaire survey. Subjects for the study were recruited from clients requesting TOP at the Gynaecology clinic (ward 54), CHBH. They included women between 13 to 49 years, who were referred from their local clinic or General practitioner with a positive pregnancy test or a pregnancy confirmed on sonar, and were less than 20 weeks pregnant. Consenting women completed a self-administered questionnaire which assessed their demographic details, current contraceptive use, past contraceptive experience, future contraceptive plans, knowledge of emergency contraceptive pill, and the current status of the relationship, initial intention with regard to the pregnancy, and the number of sexual partners they had in the last year. The data was analysed using the Epi Info 6 software programme. Results There were 780 requests for TOP during the study period. Two hundred and twenty nine women were approached to participate in the study and 203 questionnaires were analysed, i.e. an 89% analysable response rate. The mean age of the respondents was 25 years (range 13 - 42 years), the mean parity was 1.3 (range 0 to 9), 35% were still in school, 28% were unemployed and 70% were financially dependent on their parents, partners, or other relatives. A total of 56% of the respondents reported that they were using contraception when they conceived. Only 11% of the respondents knew of the emergency contraception pill. Eighty two percent of the respondents knew where to obtain contraceptives and only 7% had experienced actual difficulty in obtaining contraception. However, 46% thought they received „too little‟ information about contraception at their local clinic and 26% said that the contraceptive method they received was the healthcare provider‟s choice. Up to 47% of the respondents were either unsure of the contraceptive method they would use or would not use any contraception following the TOP. However, 43% would use a highly reliable contraceptive method (the oral contraceptive pill, injectable contraceptive, or sterilisation). Regarding the status of the relationship which resulted in the pregnancy, 44% were no longer in a permanent relationship (41% were and 11% never were). Twenty two percent of the respondents initially wanted the pregnancy. Conclusions Twenty two percent of the respondents initially wanted the pregnancy and would not have been helped by better provision of contraception. A large number of respondents reported contraceptive failure. Knowledge of emergency contraception was poor, and its use should be better promoted for cases of contraceptive failure. It is alarming that up to 47% of the clients could not use contraception in the future. Perhaps more time should be spent on contraceptive counselling and initiation of a method on site, with referral and follow-up at primary health clinics to improve uptake of contraception. Only 2.5% of the respondents were having a repeat TOP.
M.Med. (Obstetrics and Gynaecology), Faculty of Health Sciences, University of the Witwatersrand,2008
Keywords: contraception; abortion; termination of pregnancy